Synthesis of a carboxylic acid-based ruthenium sensitizer and its applicability towards Dye-Sensitized Solar Cells - Pirashanthan, A.; Thanihaichelvan, M.; Mariappan, K.; Velauthapillai, D.; Ravirajan, P.; Shivatharsiny, Y. (University of Jaffna, 2021)
This work reports the synthesis of ruthenium based Ru(bpy)2(dcbpy)(ClO4)2[(bpy)2,2′ -bipyridine;dcbpy = 4,4′ - dicarboxy-2,2′ -bipyridine] (RuC) dye and its application in solid and liquid state Dye-Sensitized Solar Cells (DSSCs). Synthesis resulted with high-pure orange coloured dye with a high yield percentage of 45%. The dye was characterized via Nuclear Magnetic Resonance (NMR) spectroscopy, Mass spectroscopy, Cyclic Voltammetry (CV) and UV–vis spectroscopy. The calculated bandgap (Eg) of 2.38 eV from absorbance spectra of pure RuC in ethanol solution showed best proximity with the data obtained from CV measurements. The RuC showed strong absorption in near UV region with the highest molar extinction coefficient (MEC) of 14,746 M− 1 cm− 1 at 463 nm. Plateau of over 80% of External Quantum Efficiency (EQE) spectra reveals the efficient carrier generation of RuC in near UV region. Carboxylic acid groups of RuC provide the potential for enhanced electron transfer from TiO2 surface, and an increased electron density at the interface leads to higher current density. The RuC sensitized solid and liquid state DSSCs exhibited a short circuit current density (JSC) over 3.04 mA/cm2 and 5.82 mA/cm2 , and power conversion efficiency (PCE) of 1.2% and 1.8% respectively under simulated Air Mass 1.5 irradiation (100 mWcm− 2).
Keywords: Ruthenium dye; Titanium dioxide; Solar cells; Mass spectrum; Cyclic voltammetry; External quantum efficiency